Analisis Faktor-Faktor yang Mempengaruhi Produksi Usahatani Padi Sawah di Desa Bumiraya Kecamatan Andoolo Kabupaten Konawe Selatan - Untari, Evi; Surni, Surni; Dirgantoro, Muhammad Arief (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to determine the influence of factors of production towards results (of production) in the village of paddy rice farming Bumiraya Southern District of Andoolo Konawe. Determination of the sample using random sampling techniques (simple random sampling), determination of a sample of 15 percent representing 41 families of the number of population is 274 households (Arikunto, 2006). Data were analyzed using Multiple Regression analysis NonLinear with the help of SPSS version 16.0. The results showed that the factors of production land area significantly affected the production of paddy rice farming seen from the level Î± = 0.05> 0.00 significance level. whereas the factors of production such as seeds, fertilizer urea, TSP fertilizer, NPK fertilizer, pesticides and labor did not affect the production of paddy rice farming in the village Bumiraya Southern District of Andoolo Konawe.